GANGGUAN KESEHATAN MATA PADA PEKERJA DI BENGKEL LAS LISTRIK DESA SEMPOLAN, KECAMATAN SILO, KABUPATEN JEMBER - Yunita Satya Pratiwi* Wahyudi Widada** Zuhrotul Eka Yulis A.*** (The Indonesian Journal of Health Science, 2015)
This study was an observational study that aims to identify eye health disorders on electric welding workers and related factors in Welding Power Sempolan Village, District Silo, Jember, because there were 12 sites of electric welding with 3 to 4 workers in each welding. Therefore there were 38 workers in all weldings. Those workers were selected as the research samples. Research instrument was questionnaire and observation sheet. The results showed that the majority (47.4%) of respondents had a working life of 1 to 5 years, and 66% were not disciplined in the use of personal protective equipment (PPE) welding glasses correctly. Based of that, all workers had felt and experienced eye health problems as a result of the activities of the welding process. Data analysis was logistic regression showed that the use of factors of personal protective equipment (PPE) electric welding goggles had had the most dominant relationship with the incidence of eye health problems (pvalue = 0.008; α = 0.05) with an odds ratio (OR) = 27 which means that the electric welding workers were undisciplined wear personalprotective equipment (PPE) correctly had 27 times greater would experience risk of eye health problems when compared to the discipline after the controlled variable of working life. This research was conducted in an effort to improve the health of the eye on the electric welding workers. Hopefully, this study can be used as a basis to provide appropriate solutions to overcome the problems of workplace accidents (eye health problems) on electric welding workers.